Assessing display variability in wild brown anoles Anolis sagrei using a mechanical lizard model - Sarah R. PARTAN, Peter OTOVIC, Virginia L. PRICE, Scott E. BROWN (Current Zoology, 2011)
Signals used for species identity ought to be highly stereotyped so as to facilitate immediate recognition by conspecifics. It is surprising therefore to find variability in putative species signature displays. The brown anole Anolis sagrei has a high degree of variability in its signature bobbing display. In this study we collected descriptive data on variability in the temporal structure of wild brown anole bobbing patterns, finding that no two displays analyzed had the same temporal structure, and we also tested whether wild brown anoles prefer the signature display over an alternate display pattern by using mechanical robot playbacks in the field. As a response metric we assessed whether or not the lizards showed social responses (pushup, dewlap extension, or head-nod) in response to the robotic presentations. We found that the lizards responded slightly more to the signature than to the alternate pattern, providing support for the idea that despite the variability seen in displays, the signature pattern is meaningful to them. We tested two other independent variables: speed of the display and elevation of the robot during its display, neither of which was significant. Dewlap extensions were given predominantly by adult males and were more likely to be given in the breeding season than the nonbreeding season. Pushups and head-nods were given equally by males and a combined class of females and juveniles, and were not seasonal. Head-nods increased after the robot turned off, suggesting that they may be used in a conversational turn-taking style during communication [Current Zoology 57 (2): 140–152, 2011].